Accelerating Cell Therapy for Stroke in Japan: Regulatory Framework and Guidelines on Development of Cell-Based Products. Issue 4 (April 2018) - Houkin, Kiyohiro; Shichinohe, Hideo; Abe, Koji; Arato, Teruyo; Dezawa, Mari; Honmou, Osamu; Horie, Nobutaka; Katayama, Yasuo; Kudo, Kohsuke; Kuroda, Satoshi; Matsuyama, Tomohiro; Miyai, Ichiro; et al.
Abstract : Supplemental Digital Content is available in the text.